Characterization of aroma-active compounds in Chinese quince (Pseudocydonia sinensis Schneid) by aroma dilution analyses. (March 2018) - Choi, Ji Young; Lee, Sang Mi; Lee, Hyong Joo; Kim, Young-Suk
Abstract: Aroma-active compounds in the peel and pulp of Chinese quince fruits were extracted by high-vacuum distillation (HVD) and headspace solid-phase microextraction (HS-SPME) methods and identified by gas chromatography-olfactometry (GC-O) combined with aroma dilution analyses. Ethyl 2-methylpropanoate, ethyl ( E )-2-butenoate, ethyl 2-methylbutanoate, methional, ( Z )-3-hexenyl acetate, β-ionone, ethyl nonanoate, and γ-decalactone were detected as the potent aroma-active compounds (log3 FD factors ≥ 5) in the peel of Chinese quince, while hexanal, ( Z )-3-hexenal, and ( Z )-3-hexenol, which have a green odor note, were potent aroma-active compounds with high log3 FD factors (≥ 3) in the pulp of Chinese quince. In particular, ethyl propanoate, ethyl ( E )-2-butenoate, and ( Z )-3-hexenyl acetate—which had sweet and fruity aroma notes with relatively high FD factors—were detected in the samples extracted by HS-SPME. Graphical abstract: Highlights: Aroma-active compounds in the peel and pulp of Chinese quince were analyzed by GC-O. The potent aroma-active compounds were determined by aroma dilution analyses. Volatile compound of Chinese quince differed between the HVS and HS-SPME extracts. Ethyl ( E )-2-butenoate, and ( Z )-3-hexenyl acetate were the potent odorants in the peel. Aroma-active compounds were more prevalent in the peel than in the pulp.